1980
DOI: 10.1021/ja00543a038
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-catalyzed organic synthesis: NADH regeneration by using formate dehydrogenase

Abstract: Existing methods for regeneration of NADH from NAD"1" for use in organic synthetic procedures based on NADH-dependent enzymes all have disadvantages.2,3 Here we describe the use of (1) Supported by the National Institutes of Health (Grant GM 26543).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(64 citation statements)
references
References 0 publications
2
61
0
1
Order By: Relevance
“…The enzymecoupled approach is characterized by the use of a second enzyme, which catalyzes the oxidation of a cosubstrate to regenerate the reduced form of the cofactor. Formate dehydrogenase (Ernst et al, 2005;Hummel and Kula, 1989;Shaked and Whitesides, 1980;Tishkov et al, 1999) or glucose dehydrogenase (Kizaki et al, 2001;Weckbecker and Hummel, 2004) can be applied as the second enzyme for cofactor regeneration. In the substrate-coupled approach the alcohol dehydrogenase (ADH) used for the reduction reaction also catalyzes the cofactor regenerating reaction by oxidation of a second substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The enzymecoupled approach is characterized by the use of a second enzyme, which catalyzes the oxidation of a cosubstrate to regenerate the reduced form of the cofactor. Formate dehydrogenase (Ernst et al, 2005;Hummel and Kula, 1989;Shaked and Whitesides, 1980;Tishkov et al, 1999) or glucose dehydrogenase (Kizaki et al, 2001;Weckbecker and Hummel, 2004) can be applied as the second enzyme for cofactor regeneration. In the substrate-coupled approach the alcohol dehydrogenase (ADH) used for the reduction reaction also catalyzes the cofactor regenerating reaction by oxidation of a second substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, numerous efforts have been made over the past decades to accomplish in situ cofactor regeneration from their oxidized counterpart. [6][7][8][9] For example, researchers found that NAD(P)H can be successfully regenerated by introducing secondary enzymes [10][11][12] that reduce its oxidized counterpart (i.e., NAD(P) + ) or electrodes [13][14][15] with an external power supply into reaction media. However, these approaches present intrinsic drawbacks (e.g., by-product formation and requirement of secondary enzymes for biocatalytic regeneration, as well as extremely low yield and high overpotential for electrochemical regeneration) that hindered their practical application beyond the laboratory scale.…”
mentioning
confidence: 99%
“…This system has been successfully used for NADH regeneration in a membrane reactor for L-leucine synthesis (high conversion 90-99.7% maintained during more than 25 d) [5] or D-lactate synthesis (complete reaction in 7 d) [6]. The formate dehydrogenase generally used so far is specific to NAD + , but a new formate dehydrogenase has been produced [7] that is able to work with NADP + .…”
Section: Enzyme-catalyzed Regeneration Of the Cofactormentioning
confidence: 99%
“…3) was equipped with a platinum or a porous carbon felt working electrode (5). The solution circulated through this electrode, then through the membrane (4') until reaching the solution collector (6). In this case, the driving force is the pressure gradient.…”
Section: Description Of the Membrane Electrochemical Reactors (Mers)mentioning
confidence: 99%